Penggunaan Media Internet Pada Pembelajaran Keterampilan Mendengar Bahasa Jerman Siswa Kelas XI Administrasi Perkantoran 3 SMKN 1 Boyolangu - ISMAWANTO, (LATERNE, 2013)
Providing training on learning to hear it is expected that students can understand the German language better and to improve learning outcomes. Exercise is a repetition and strengthening students' understanding of the German language learning. With this expected impression on students at the time of writing more in-depth lessons and memorable. Students are also encouraged to find their own materials or sources of knowledge with regard to what they learned. The formulation of the problem of the above background is How a class XI student learning outcomes Administration 3 SMKN1 Boyolangu in listening skills through exercises from the internet. The aim of this research is to describe the learning outcomes of students in listening skills through exercises from the internet. The study design used is a researcher, one group pre-test post-test design. In this study there is only one class of experiments were sampled by random sampling. The study lasted for two weeks. Data retrieval research is pre-test and post-test. The results obtained from the T-test = 45.17 and t count TTable = 2.034. It can be concluded that thitung> ttable 45.17> 2.034. This means an increase in class XI listening skills AP3 SMKN I Boyolangu after using exercise to hear the German language from the internet.